ANALYSIS OF BEAM ANGLE INFLUENCE AND ITS RELATIONSHIP TO BACKSCATTER USING ANGULAR RANGE ANALYSIS: ANALISIS PENGARUH DAN HUBUNGAN BEAM ANGLE TERHADAP HAMBUR BALIK DENGAN METODE ANGULAR RANGE ANALYSIS - Dhea Ananda Masdar; Henry Munandar Manik; Totok Hestirianoto (Jurnal Teknologi Perikanan dan Kelautan, 2026)
The shallow waters of Pari Island exhibit diverse seafloor substrates, making them an ideal site for hydroacoustic seabed characterization studies. This study aims to analyze backscatter variations at different beam angles and evaluate the mathematical relationship between beam angle and backscatter intensity using the Angular Range Analysis (ARA) method. The novelty of this study lies in modeling the beam angle-backscatter relationship in tropical shallow-water environments in Indonesia, which remains relatively limited in the literature. Data were acquired using a 300 kHz Teledyne Reson SeaBat T50-R Multibeam Echosounder (MBES) and processed using the Fladermaus Geocoder Toolbox (FMGT), while surface sediment samples were collected using a Van Veen grab sampler. ARA generated angular response curves showing that the highest backscatter values consistently occurred at nadir (0°) and gradually decreased toward grazing angles. Backscatter values ranged from -19.27 dB to -37.41 dB. The average backscatter values for sand, silty sand, and coral fragments or rock were -32 dB, -34 dB, and -30 dB, respectively. The beam angle–backscatter relationship was modeled using second- and third-order polynomial regressions, yielding coefficients of determination of 0.9064-0.998 and 0.9251-0.999, respectively. The results indicate that changes in beam angle adequately explain the backscatter variation. These findings demonstrate that ARA is effective for characterizing backscatter angular response patterns and support MBES data interpretation in tropical shallow waters.